Music enhances performance and perceived enjoyment of sprint iterval exrcise - Stork, M. J.; Kwa, M. Y. W.; Gibala, M. J.; Martin Ginis, K. A. (Medicine & Science in Sports & Exercise, 2015)
Introduction: Interval exercise training can elicit physiological adaptations similar to those of traditional endurance training, but with reduced time. However, the intense nature of specific protocols, particularly the "all-out" efforts characteristic of sprint interval training (SIT), may be perceived as being aversive. The purpose of this study was to determine whether listening to self-selected music can reduce the potential aversiveness of an acute session of SIT by improving affect, motivation, and enjoyment, and to examine the effects of music on performance.